PENINGKATAN PENDAPATAN MASYARAKAT JATILUWIH MELALUI PENGEMBANGAN CINDERAMATA LOKAL - Putra, Agus Muriawan (Buletin Udayana Mengabdi, 2012)
As one of the tourism destinations, the society of Jatiluwih is required to take care of the continuity of natural environment and culture, because besides as tourism destintion, Jatiluwih is also recognized as World Cultural Heritage by UNESCO. The society culture of Jatiluwih is very famous on the agricultural culture required to be preserved and developed because between society lives and farming cannot be separated in Jatiluwih. Therefore, the growth of Jatiluwih as tourism destination is expected to earn the sustainability. This can be done, by giving more involment toward the local organization namely “Kelompok Sadar Wisata” Tourism Awareness Group.